An Assessment on The Reading Interest Of Third Year Students Of Maximo L. Gatlabayan Memorial National High School: A Basis In Selecting Supplementary Reading Materials In English - CORPUZ, GERRY CEL E. (International Journal of Arts, Sciences and Education, 2022)
This study focused on the Assessment on The Reading Interest Of Third Year Students Of Maximo L. Gatlabayan Memorial National High School: A Basis In Selecting Supplementary Reading Materials In English; School Year 2012-2013. Specifically, it aimed to assess the reading interests of the third year high school students of Maximo L. Gatlabayan Memorial National High School with the end view of making it the basis for the selection of relevant instructional materials in reading. This study utilized all the third year students of Maximo L. Gatlabayan Memorial National High School enrolled for the Academic Year 2012-2013. The researcher used the descriptive type of research. Hillway pointed out that a descriptive survey method is a process of learning pertinent information about an existing situation. In this study, it was used in order to obtain precise and valuable information about the Health Practices of the third year students of Maximo L. Gatlabayan Memorial National High School.